Medical and care compunetics 3 - Bos, Lodewijk (IOS Press, 2006)
For citizen/patient-related information, it is necessary to use the latest medical and care compunetics. This publication covers aspects concerning information supply to patient and professional; electronic health records, its standards, its social implications; and developments in medical and care compunetics.
"This book accompanies the third annual ICMCC Event."--Page vii.
Keywords: Medical informatics -- Congresses.; Telecommunication in medicine -- Congresses.; Medical telematics -- Congresses.; Telecommunication in medicine.; Medical Informatics; Medical Informatics Applications; Computer Communication Networks; Telemedicine; Remote Consultation; Médecine -- Informatique -- Congrès.; Télémédecine -- Congrès.; Télématique médicale -- Congrès.; Médecine -- Informatique.; Télémédecine.; TECHNOLOGY & ENGINEERING -- Biomedical.; MEDICAL -- Family & General Practice.; MEDICAL -- Allied Health Services -- Medical Technology.; MEDICAL -- Biotechnology.; MEDICAL -- Lasers in Medicine.; Medical informatics; Medical telematics; Telecommunication in medicine; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.